Nintedanib and a bi-specific anti-VEGF/Ang2 nanobody selectively prevent brain metastases of lung adenocarcinoma cells - Kovalchuk, Bogdana; Bergmeister-Berghoff, Anna Sophie; Karreman, Matthia A.; Frey, Katharina; Piechutta, Manuel; Fischer, Manuel; Grosch, Julia Katharina; Heiland, Sabine; Breckwoldt, Michael O.; Hilberg, Frank; Wick, Wolfgang; Winkler, Frank (Clinical & experimental metastasis, 2020)
Brain metastases (BM) are an ever-increasing challenge in oncology, threatening quality of life and survival of many cancer patients. The majority of BM originate from lung adenocarcinoma, and stage III patients have a risk of 40-50% to develop BM in the first years of disease onset. As therapeutic options are limited, prevention of their occurrence is an attractive concept. Here we investigated whether Nintedanib (BIBF 1120), a tyrosine kinase inhibitor (TKI) targeting the VEGF pathway approved for lung adenocarcinoma, and the dual anti-VEGF-A/Ang2 nanobody BI836880 have the potential to prevent BM formation. A mouse model of brain metastasis from lung adenocarcinoma was used in which tumor cells were injected intracardially. Metastases formation occurred inside and outside of the brain and was followed by MRI, IVIS, and immunohistochemistry. BM were reduced in volume and number by both Nintedanib and the dual anti-VEGF-A/Ang2 nanobody, which translated into improved survival. Both compounds were able to normalize cerebral blood vessels at the site of brain metastatic lesions. Extracranial metastases, however, were not reduced, and meningeal metastases only partially. Interestingly, unspecific control IgG also lead to brain vessel normalization and reduction of brain and meningeal metastases. This data indicates a brain-specific group effect of antiangiogenic compounds with respect to metastasis prevention, most likely by preventing an early angiogenic switch. Thus, Nintedanib and BI836880 are promising candidates for future BM preventive study concepts in lung adenocarcinoma patients.